Biomechanics associated with bone stress injury in athletes differ by proximal and distal anatomical locations: a cross-sectional analysis - Gaudette, L. W.; Ackerman, K. E.; Bouxsein, M. L.; Bruneau, M. M.; de Souza Junior, J. R.; Garrahan, M.; Gehman, S.; Hughes, J. M.; Outerleys, J.; Willy, R. W.; Davis, I. S.; Popp, K. L.; et al. (BMJ Open Sport & Exercise Medicine, 2025)
Background Bone stress injury (BSI) is a common overuse injury in female athletes that can occur in a variety of bones, including both proximal (pelvis, sacrum, femoral neck) or distal (tibia, fibula, metatarsals) locations. Prior work has demonstrated differences in running biomechanics in those with BSI; however, this was not separated by anatomy. We hypothesised that both female athletes with distal BSI and female athletes with proximal BSI would have lower cadence, higher centre of mass (COM) and lower duty factor than those without prior BSI.